Some comments on total factor productivity and its growth in India - Dube, Partha Partim (Goodwood Publishing, 2022)
Purpose: This paper considers the prospects for constructing a model of Total Factor Productivity (HenceTFP) of investment, technological progress and growth of the technological share in TFP. Research Methodology: This paper tries to understand the driving factors of TFP by establishing the relations between the factors. Results: Models consider emphasizing investment, technological progress and its impact on TFP and also on relation of investment with TFP and growth of technological share in TFP through the experience process. The claims in models provide a relation between investment and TFP; a relation between technological efficiency and technological progress is formed and their effect on TFP is also established. Limitations: The limitations of the study are that we have considered selected parameters of TFP only. To study TFP completely a fuller model is needed where all the parameters would be considered. Contribution: This study will help to understand TFP and its internal dynamics. A quotient between technological progress and investment is constructed that hampers the growth of technological progress. This gives a caution to the financial institutions about the enhancement of the quotient.